Synodality and interreligious developments in Kairos theology: Pathways for today’s Catholic Church - Haworth, Marcus Timothy (Hervormde teologiese studies, 2025)
In April 2021, the late Pope Francis approved the initial programme for the celebration of the 16th Ordinary General Assembly of the Synod of Bishops within the Catholic Church with the theme ‘For a Synodal Church: Communion, Participation, and Mission’. While the timeline for the Synod on Synodality, the colloquial appellation given to this event, was extended until 2024, its goals did not deviate from those laid out in this initial programme. In this article, the author takes one of these goals, and a neglected one at that – dialogue in church and society, with a particular focus on interreligious engagement – as his point of departure. In doing so, the author examines the import of the 1985 South African Kairos Document and the interreligious developments in Kairos theology it spawned in the 2009 Israel-Palestine Kairos Document for more faithfully enacting the synodal missional ecclesiology called for by the 2021–2024 Synod on Synodality within the Catholic Church today. Contribution: The author argues that Kairos theology offers a number of promising interreligious pathways for furthering the development of a Catholic synodal missional ecclesiology in the present, in part because its means of production is inherently of the people – operating as a protological and prototypical form of what an authentic Catholic synodal missional ecclesiology is and can be – and also because this form of being and doing church has practical, pastoral, and theological applications for advancing the shared experiences of dialogue and commitment that Christian believers share with those of other religions and with non-believers alike.